Pendidikan Keluarga Berbasis Gender dalam Perspektif Masyarakat Desa Ranuwurung Kecamatan Gading Kabupaten Probolinggo - Ahmad Khumaidi (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
Abstract The family is the first and foremost center of education. It is in this family that children first receive education and guidance. Family education is a very important education, especially Islamic education, which absolutely must be done by both parents from an early age to adulthood. In addition, the family also functions as the foundation for the formation of the child's personality. In this case, the role of parents as first and foremost educators is needed. The focus of this study is to find out in detail about the relationship between husband and wife and between sons and daughters in the family with the following problem formulation: (1) What are the views of the people of Ranuwurung Village, Gading District, Probolinggo Regency regarding the obligation to educate children for both parent?; (2) What is the view of the people of Ranuwurung Village, Gading District, Probolinggo Regency regarding the example that must be given by both parents?; (3) What is the view of the people of Ranuwurung Village, Gading District, Probolinggo Regency regarding the justice of parents in providing education to all children? From the analysis of the data obtained, it can be concluded that the views of the Ranuwurung village community regarding the obligation to educate children for parents are something that must be carried out. Because they think that children are the responsibility entrusted by God to be given education and teaching. According to those who have the right or obligation to educate their children, it is the parents. Keywords: Education, Family, Gender